Rheological properties of rice starch at high moisture contents during twin-screw extrusion - Akdogan, Hulya (2011)
A semi-empirical model to predict the apparent viscosity function of high moisture rice starch melt was developed. The model coupled the influence of extruder operating parameters on characteristics of the fluid and on conditions of rheological measurements. The model for apparent viscosity considered power law dependency of shear rate, and exponential dependency of temperature, moisture content, and screw speed. A MPC/V-30 co-rotating twin-screw extruder and a slit die/torque rheometer combination were used. Operating parameters varied between 175 and 275 rpm for the screw speed, 80 to 100 °C for extruder and slit die temperatures, 570 to 650 g/kg solution for moisture content, and 2 to 7 kg/h for the mass flow rate. The fit between the experimental results and model was good. Die temperature was the most important parameter influencing the viscosity of rice starch during extrusion.